Fracionamento de Ba, Cr, Cu, Ni e Zn em solos tratados com lodo de esgoto em experimentos de longa duração - Santos, Larissa Macedo dos (2010)
As the agronomic importance of the provision of agricultural sewage sludge, and its growing concerning environmental point of view, in this work decomposition procedures of soil samples subjected to the addition of sewage sludge were evaluated for total content determination of Ba, Cd, Cr, Cu, Ni, Pb and Zn; the contents of the aforementioned elements present in two tropical soils, Typic Eutrorthox and Typic Haplorthox, collected through 11 years of experiment were determined and compared, in order to evaluate the accumulation and dynamic of these analytes; the availability of Ba, Cr, Cu, Ni and Zn in the soils subjected to the addition of sewage sludge after 11 consecutive years were evaluated by means of sequential extraction, and a methodology for determining the availability of elements potentially toxic in soils subjected to the addition of sewage sludge from the assessment of humic fractions, fulvic acid 1, fulvic acid 2, humic acid and humin + mineral obtained during the chemical fractionation of soil organic matter was proposed. The use of reversed aqua regia, H2O2, predigestion and agitation after the addition of HF presented above of 90% of recovery for Ba, Cd, Cr, Cu, Ni, Pb and Zn and the complete dissolution of silicate compounds for the tropical evaluated soils. The addition of sludge resulted in significant increase of total contents of Cr, Cu, Ni and Zn to Typic Eutrorthox and Ba, Cu and Zn to Typic Haplorthox. Availability studies presented significant amount of Cr, Cu, Ni and Zn bounded to the Mn and Fe oxides and residual fractions, indicating the low availability of these elements in the evaluated soils. The chemical fractionation of soil organic matter obtained results confirm the high concentration of potentially toxic elements in the oxides in the Typic Eutrorthox soil and in the humic acid in the Typic Haplorthox soil. Although the sewage sludge added to soil increase the levels of potentially toxic elements, these are present in the most stable fractions of soil. In other words, less available or less mobile.